Pengembangan Media Scratch Berbasis Active Learning pada Pembelajaran Matematika di Sekolah Dasar - Annisa Anita Dewi, Annisa Anita Dewi; Nida Sopiah Zulfa, Nida Sopiah Zulfa; Karlimah, Karlimah (Jurnal Didaktika Pendidikan Dasar, 2025)
This research aims to develop Scratch media using active learning strategies as a catalyst for learning, teaching mathematics learning in elementary schools, through the development of Scratch media with active learning strategies students have a lot of active involvement resulting in increased numeracy literacy competency achievement. Scratch media development with active learning strategies provides a stimulus for learning for transfer, to master knowledge and skills not only limited to mastery of learning materials. This study used qualitative methods with a design-based research approach. Data collection techniques with observation, documentation and in-depth interviews to explore information more deeply and thoroughly. The data analysis technique used was Miles and Huberman triangulation. The results showed that the use of Scratch media had a positive impact on students’ understanding of multiplication concepts. Scratch media integrated with active learning strategies in mathematics learning in elementary schools helps students visualize the concept of multiplication, increase learning motivation, encourage active participation in learning, stimulate and have more impact so that it has implications for increased learning outcomes. It can be concluded that the development of scratch media based on active learning in learning mathematics in elementary schools has an impact on increasing learning outcomes and learning motivation.